Relações étnico-raciais e educação infantil: dizeres de crianças sobre cultura e história africana e afro-brasileira na escola - Rocha, Nara Maria Forte Diogo (2015)
The study investigates ethnic-racial relations in the teaching of African culture and african-Brazilian from the perspective of childhood cultures in the context of early childhood education. It takes into account on the one hand, the historical moment of tackling racism in Brazil, translated into affirmative action policies, most notably education Law 10,639, and on the other hand the methodological discussion on research with children emphasizing the seizure child view. As a general objective aims to understand how children mean the knowledge on African history and culture and african-Brazilian school. Specifically, it aim to discuss the role of the early childhood school as a mediator of knowledge on African and african-Brazilian culture; to understand the movement of meanings attributed by children to ethnic and racial relations in schools rites and to thematize the experience of racial relations in the school context from the perspective of childhood cultures The theoretical perspectives adopted are the Cultural Studies, Postcolonial Studies and South Epistemologies Studies and the Sociology of Childhood and the Historical-Cultural Psychology. It's ethnographic case study carried out in a private school in kindergarten and elementary school in Fortaleza-CE. The corpus consisted of field diaries and video recordings of the activities performed by children as well as transcribed interviews (families and school staff). With regard to children, peer’s culture category allowed the understanding of the training criteria, maintenance and dynamics of their groups: previous cohabitation, gender and presence of disability. The ethnic and racial identity was taken by children as a control strategy in the peer group, which was neutralized by the school, and as identification of self and other. The significance of African history and culture and african-Brazilian is marked by dialogued heteroglossia and selective invisibility, organizing itself as a performative and paradoxical way. It is concluded that the placements of children ranged from positive identification with the indigenous and European culture at the expense of black/African culture, reproducing interpretively the paradoxes perceived in how African culture is transmitted in school and in Brazilian society. Finally, the thesis is that the meanings expressed by the children are organized around paradoxes that brings out the tensions, dilemmas and conflicts within an anti-racist education in Brazilian society.